Reconceiving midwifery - Benoit, Cecilia M., 1954-; Bourgeault, Ivy Lynn, 1967-; Davis-Floyd, Robbie (McGill-Queen's University Press, 2004)
Midwifery in the developed world is in a state of ferment and change - a phenomenon referred to as the 'new midwifery'. This title offers analysis of the new midwifery as it is practised and reflects on regional differences in the emerging profession, providing a systematic account of its historical, local and international roots and more.